2017
DOI: 10.1038/s41598-017-08238-w
|View full text |Cite
|
Sign up to set email alerts
|

Sealing the Pores of PEO Coating with Mg-Al Layered Double Hydroxide: Enhanced Corrosion Resistance, Cytocompatibility and Drug Delivery Ability

Abstract: In recent years, magnesium (Mg) alloys show a promising application in clinic as degradable biomaterials. Nevertheless, the poor corrosion resistance of Mg alloys is the main obstacle to their clinical application. Here we successfully seal the pores of plasma electrolytic oxidation (PEO) coating on AZ31 with Mg-Al layered double hydroxide (LDH) via hydrothermal treatment. PEO/LDH composite coating possess a two layer structure, an inner layer made up of PEO coating (~5 μm) and an outer layer of Mg-Al LDH (~2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 39 publications
(39 reference statements)
5
55
0
Order By: Relevance
“…Herein, we report a facile hydrothermal measurement to in-situ growth of NiAl-LDH nanocomposite on Mg alloy by use of alkaline solutions with three different nickel salts for preparation of a highly enhanced corrosion-resistant coating with an extraordinary low corrosion rate ( Figure 1 ). The NiAl-LDH coating prepared by nickel carbonate exhibits uniformly and vertically aligned nanoarrays with an extremely large impedance modulus at a low frequency of 0.1 Hz (| Z | f = 0.1 Hz ), 11.6 MΩ cm 2 , and a significantly low j corr down to 1.06 nA cm −2 in 3.5 wt % NaCl corrosive electrolyte, which outperforms the values of the foregoing achieved LDH coating on Mg alloy ( Table 1 ) [ 8 , 10 , 13 , 14 , 16 , 17 , 18 ]. The NiAl-LDH coatings were characterized, and the enhanced corrosion inhibition mechanism was proposed and discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we report a facile hydrothermal measurement to in-situ growth of NiAl-LDH nanocomposite on Mg alloy by use of alkaline solutions with three different nickel salts for preparation of a highly enhanced corrosion-resistant coating with an extraordinary low corrosion rate ( Figure 1 ). The NiAl-LDH coating prepared by nickel carbonate exhibits uniformly and vertically aligned nanoarrays with an extremely large impedance modulus at a low frequency of 0.1 Hz (| Z | f = 0.1 Hz ), 11.6 MΩ cm 2 , and a significantly low j corr down to 1.06 nA cm −2 in 3.5 wt % NaCl corrosive electrolyte, which outperforms the values of the foregoing achieved LDH coating on Mg alloy ( Table 1 ) [ 8 , 10 , 13 , 14 , 16 , 17 , 18 ]. The NiAl-LDH coatings were characterized, and the enhanced corrosion inhibition mechanism was proposed and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MgFe-LDH and MgCr-LDH films were also obtained on anodized AZ31 Mg alloy by in-situ growth measurement [ 10 ]. However, the orders of magnitude of the j corr of these in-situ grown LDH coatings are higher than −8, mostly range from −5 to −7 ( Table 1 ) [ 8 , 11 , 12 , 13 , 14 ]. To break the bottleneck of j corr , it is advisable to prepare carbonate-based LDHs film by attempting more different divalent or trivalent metallic cations.…”
Section: Introductionmentioning
confidence: 99%
“…S3 ). Our previous study revealed that cell viability decreased significantly when concentration of Mg 2+ higher than 20 mM or pH value higher than 8.5 [ 37 ]. The extract of pure Mg would experience a severe change of Mg 2+ concentration and pH value, thus leading to a severe cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated temperatures associated with the formation of PEO–LDH composite coatings would lead to a mismatch between the dissolution of PEO layers and the growth of Mg–Al LDH film [ 84 , 85 , 86 , 87 , 88 , 89 ]. This deficiency would restrict the large improvement in the protective properties of these materials.…”
Section: Corrosion Performance Of Ldh/anodic Film Compositesmentioning
confidence: 99%
“…Second, if the dissolution rate of the PEO coating is identical to the growth rate of the LDH film, this may cause a certain improvement in the protective properties due to the partial sealing of structural defects of PEO coating by LDH films. As an example, Peng et al [ 85 ] made a Mg–Al LDH film on the PEO-coated AZ31 Mg alloy by hydrothermal treatment at 293 K for 12 h using a solution with a pH of 12.8. PDP results in a phosphate-buffered saline solution indicated that the i corr of the PEO coating was only reduced from 9.45 × 10 −6 A cm −2 to 3.92 × 10 −6 A cm −2 upon the application of Mg–Al LDH film on the surface of PEO coating, suggesting a slight improvement in the corrosion resistance was achieved.…”
Section: Corrosion Performance Of Ldh/anodic Film Compositesmentioning
confidence: 99%